GOOGLE TRANSLATE'S SPEECH-TO-TEXT TOOL AS A PRONUNCIATION COACH? STUDENTS SHARE THEIR VIEWS - Wahyu Andi Pratama; Ashari Ashari; Erna Wardani (LEAD (Language, Education and Development), 2024)
This study explores students' perceptions of using Google Translate’s Speech-to-Text feature for learning English pronunciation. Using a descriptive qualitative method, the research was conducted with seven purposively selected X TKJ 5 (Computer and Network Engineering) students at SMK HKTI 2 Purwareja Klampok during the 2023/2024 academic year. Data were collected through interviews, questionnaires, and observations, and analyzed using Miles and Huberman’s qualitative approach. The findings reveal that students had predominantly positive perceptions. They found Google Translate’s Speech-to-Text enjoyable, engaging, and more effective than traditional methods. Observational data confirmed students' enthusiasm, while 71.4% appreciated its low data consumption and all students (100%) agreed it effectively identified pronunciation errors and corrections. Additionally, students highlighted the tool's ease of use, flexibility, and user-friendly interface, affirming its value as an effective medium for learning pronunciation.